2020
DOI: 10.1101/2020.03.24.004051
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ab-Ligity: Identifying sequence-dissimilar antibodies that bind to the same epitope

Abstract: Motivation: Solving the structure of an antibody-antigen complex gives atomic level information of the interactions between an antibody and its antigen, but such structures are expensive and hard to obtain. Alternative experimental sources include epitope mapping and binning experiments which can be used as a surrogate to identify key interacting residues. However, their resolution is usually not sufficient to identify if two antibodies have identical interactions. Computational approaches to this problem have… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…The paratopes of K8 and K92 contain 18 and 10 residues, respectively, which are within the typical range of antibody paratope sizes ( Figure 3—figure supplement 4A ). Given this similarity in size, we searched for structurally and physicochemically similar antibody paratopes from the 924 antibody complexes but no similar paratope sites were found ( Wong et al, 2020 ). While the limited examples preclude firm conclusions, this lack of similarity could be due to either the unusual fold of the knob domains or the differences in paratope amino acid composition.…”
Section: Resultsmentioning
confidence: 99%
“…The paratopes of K8 and K92 contain 18 and 10 residues, respectively, which are within the typical range of antibody paratope sizes ( Figure 3—figure supplement 4A ). Given this similarity in size, we searched for structurally and physicochemically similar antibody paratopes from the 924 antibody complexes but no similar paratope sites were found ( Wong et al, 2020 ). While the limited examples preclude firm conclusions, this lack of similarity could be due to either the unusual fold of the knob domains or the differences in paratope amino acid composition.…”
Section: Resultsmentioning
confidence: 99%
“…Antibodies from different clonotypes have been observed to converge on the same binding site. [28][29][30][31] We hypothesize that these functionally convergent antibodies may use the same paratope for interaction, and examined SAbDab 32 for evidence that antibodies with similar paratopes bind to the same epitope. We defined the epitope and paratope as those residues with any atom within 4.5 Å of any residue in the cognate antibody or antigen, respectively, and consider only the heavy chains of the antibodies because in most BCR sequencing experiments only heavy chain sequences are available.…”
Section: Epitope Convergence Can Be Identified At the Level Of Paratomentioning
confidence: 99%
“… 5 , 10 The majority of antibodies binding to the same epitope in antibody-antigen complex structures in the Structural Antibody Database (SAbDab, a database of experimentally solved antibody and antibody-antigen complex structures) have highly similar CDRH3s. 28 However, it has also been observed that multiple clonotypes may converge on the same epitope. For example, Scheid and colleagues identified clonotypes from distinct immunoglobulin heavy chain variable (IGHV) gene subgroups converging on the CD4 binding site in gp120.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The paratopes of K8 and K92 contain 18 and 10 residues, respectively, which are within the typical range of antibody paratope sizes (Supplementary 2.14). Given this similarity in size, we searched for structurally and physicochemically similar antibody paratopes from the 924 antibody complexes but no similar paratope sites were found (Wong et al, 2020). While the limited examples preclude firm conclusions, this lack of similarity could be due either to the unusual fold of the knob domains or to differences in paratope amino acid composition.…”
Section: Functional Characterisation Of Anti-c5 Bovine Knob Domain Pementioning
confidence: 99%